Respuesta :
[tex]D: x \neq 2 \\ \\ \frac{2}{3(x-2)}=4x \\ \\ \frac{2}{3x-6}=4x \\ \\ 4x(3x-6)=2 \\ \\ 12x^{2}-24x=2 \\ \\ 12x^{2}-24x-2=0 \\ \\ 6x^{2}-12x-1=0 \\ \\ \Delta=(-12)^{2}-4*6*(-1)=144+24=168 \\ \\ \sqrt{\Delta} =2 \sqrt{42} \\ \\ x_{1}= \frac{12-2 \sqrt{42} }{12}= \frac{6- \sqrt{42} }{6} \\ \\ x_{2}= \frac{12+2 \sqrt{42} }{12} = \frac{6+\sqrt{42}}{6} [/tex]
2 / 3 ( x - 2 ) = 4x
Simplify both sides of the equation.
2/3(x−2)=4x
Simplify:
23(x−2)=4x
(2/3)(x)+(2/3)(−2)=4x(Distribute)
23x+(−4/3)=4x
Subtract 4x from both sides.
2/3x+−4/3−4x=4x−4x
−10/3x+−4/3=0
Add 4/3 to both sides.
−10/3x+−4/3+4/3=0+4/3
−10/3x=4/3
Multiply both sides by 3/(-10).
(3/−10)*(−10/3x)=(3/−10)*(4/3)
x = −2/5
Simplify both sides of the equation.
2/3(x−2)=4x
Simplify:
23(x−2)=4x
(2/3)(x)+(2/3)(−2)=4x(Distribute)
23x+(−4/3)=4x
Subtract 4x from both sides.
2/3x+−4/3−4x=4x−4x
−10/3x+−4/3=0
Add 4/3 to both sides.
−10/3x+−4/3+4/3=0+4/3
−10/3x=4/3
Multiply both sides by 3/(-10).
(3/−10)*(−10/3x)=(3/−10)*(4/3)
x = −2/5